Intestinal Morphology, Energy Availability, and Growth Performance of Broilers Treated with the Combination of Probiotic and Inulin - H. Julendra; A. Sofyan; L. Istiqomah; M. F. Karimy; Abinawanto Abinawanto; Yasman Yasman (Faculty of Animal Science, Bogor Agricultural University, 2021)
Probiotic and prebiotic or their combinations can potentially function as an alternative to antibiotics growth promoters (AGPs) for broiler. This study was designed to investigate the growth performance, intestinal microstructure, and nutrients digestibility of broilers administered with probiotics of Lactobacillus plantarum AKK30 and Saccharomyces cerevisiae B18 in combination with inulin. A total of 275 male chickens (initial bodyweight of 47±0.05 g) were reared for growth performance evaluation. At the 32-d-old, 25 male chickens were necropsied for intestinal microstructural analysis, while the other 25 male chickens were selected for evaluation of digestibility (body weight= 1525±0.08 g). Treatments of probiotics in combination with different levels of inulin consisted of control with probiotics without inulin (S0), probiotics with 0.5% of inulin (S1), probiotics with 1.0% of inulin (S2), probiotics with 1.5% of inulin (S3), and commercial probiotics without inulin (Sc), which were arranged in a completely randomized design with five replications. Results showed that body weight gain and performance index in broilers treated prebiotics in combination with 0.5% inulin (S1), 1% inulin (S2), and commercial probiotic without inulin (Sc) were significantly higher (p<0.05) than those in control broiler chickens that were treated with probiotics without inulin. Feed intake showed no differences among treatments, whereas feed conversion ratios in broiler chickens treated with the commercial probiotics (Sc) or probiotics in combination with inulin at 0.5% (S1) and 1.0% (S2) were lower than control chickens. Metabolizable energy, nitrogen retention, and villi height in chickens treated with probiotics in combination with 0.5% inulin (S1) and 1.0% inulin (S2) were higher than those in the control group. In conclusion, the administration of probiotic combined with inulin at the level of either 0.5 or 1.0% improves broiler performance, intestinal microstructure, and nutrients digestibility.